A review on computer‐aided chemogenomics and drug repositioning for rational COVID‐19 drug discovery. (22nd September 2022) - Maghsoudi, Saeid; Taghavi Shahraki, Bahareh; Rameh, Fatemeh; Nazarabi, Masoomeh; Fatahi, Yousef; Akhavan, Omid; Rabiee, Mohammad; Mostafavi, Ebrahim; Lima, Eder C.; Saeb, Mohammad Reza; Rabiee, Navid
Abstract: Application of materials capable of energy harvesting to increase the efficiency and environmental adaptability is sometimes reflected in the ability of discovery of some traces in an environment―either experimentally or computationally―to enlarge practical application window. The emergence of computational methods, particularly computer‐aided drug discovery (CADD), provides ample opportunities for the rapid discovery and development of unprecedented drugs. The expensive and time‐consuming process of traditional drug discovery is no longer feasible, for nowadays the identification of potential drug candidates is much easier for therapeutic targets through elaborate in silico approaches, allowing the prediction of the toxicity of drugs, such as drug repositioning (DR) and chemical genomics (chemogenomics). Coronaviruses (CoVs) are cross‐species viruses that are able to spread expeditiously from the into new host species, which in turn cause epidemic diseases. In this sense, this review furnishes an outline of computational strategies and their applications in drug discovery. A special focus is placed on chemogenomics and DR as unique and emerging system‐based disciplines on CoV drug and target discovery to model protein networks against a library of compounds. Furthermore, to demonstrate the special advantages of CADD methods in rapidly finding a drug for this deadly virus, numerous examples of the recent achievements grounded on molecular docking, chemogenomics, and DR are reported, analyzed, and interpreted in detail. It is believed that the outcome of this review assists developers of energy harvesting materials and systems for detection of future unexpected kinds of CoVs or other variants. Abstract : Chemogenomics and DR have become efficient approaches to screening potential therapeutic drugs for COVID‐19.